2004
DOI: 10.1023/b:phot.0000040562.34339.b3
|View full text |Cite
|
Sign up to set email alerts
|

Gas Exchange and Chlorophyll Fluorescence Response to Simulated Rainfall in Hedysarum fruticosum var. mongolicum

Abstract: The response of gas exchange and chlorophyll fluorescence along with changes in simulated rainfall were studied in water stressed plants Hedysarum fruticosum var. mongolicum (H.f.m.). Net photosynthetic rate (P N ), stomatal conductance (g s ), leaf water potential (Ψ leaf ), and apparent carboxylation efficiency (P N /C i ) were significantly increased with the increase of rainfall. However, they did not change synchronously. The complete recovery of both P N and P N /C i appeared 3 d after watering while g s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2007
2007
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 25 publications
0
9
0
Order By: Relevance
“…Auge et al (1998) observed the foliar dehydration tolerance and Liu et al (2003) measured, among other factors, stomatal conductance and leaf water potential in sand rice (Agriphyllum squarrosum) using a WAM, and observed that the increase in soil water content significantly affected the physiological traits analyzed, while the change in the photosynthesis was delayed as compared to changes in water potential. Starting the current trend for the use of WAM, Niu et al (2004) studied other aspects such as gas exchange and chlorophyll fluorescence response to simulated rainfall in plants under water stress by measuring leaf water potential. Other authors such as YuBing et al (2007), Xu and Zhou (2008), and Li et al (2010) used WAM in their research, but the suitability of the use of this type of TCP in the field has not been verified.…”
Section: Measurement Of Leaf Water Potentialmentioning
confidence: 99%
“…Auge et al (1998) observed the foliar dehydration tolerance and Liu et al (2003) measured, among other factors, stomatal conductance and leaf water potential in sand rice (Agriphyllum squarrosum) using a WAM, and observed that the increase in soil water content significantly affected the physiological traits analyzed, while the change in the photosynthesis was delayed as compared to changes in water potential. Starting the current trend for the use of WAM, Niu et al (2004) studied other aspects such as gas exchange and chlorophyll fluorescence response to simulated rainfall in plants under water stress by measuring leaf water potential. Other authors such as YuBing et al (2007), Xu and Zhou (2008), and Li et al (2010) used WAM in their research, but the suitability of the use of this type of TCP in the field has not been verified.…”
Section: Measurement Of Leaf Water Potentialmentioning
confidence: 99%
“…High xylem hydraulic conductivity enables better hydration of transpiring leaves that supports high stomatal conductance and potentially high photosynthetic efficiency (Santiago et al, ; Zhang & Cao, ; Hao et al, ). Previous studies showed that H. fruticosum has photosynthetic traits comparable with that of the C 4 plants, such as high light saturation point, low dark respiration rate, and low intercellular CO 2 concentrations (Niu et al, , ). The potentially fast growth of H. fruticosum facilitated by high hydraulic efficiency and photosynthetic capacity has likely been made possible by a relatively high soil water availability at the early stage of sand dune fixation.…”
Section: Discussionmentioning
confidence: 99%
“…Both shrub species are generally regarded as drought tolerant and well adapted to the sand dune environments. H. fruticosum is a fast‐growing pioneer species that can quickly obtain relatively large biomass and occupy a dominant position within around 3 years after planted (Niu et al, ). However, C. microphylla performs better after the fixation of the dunes and takes over the dominant position later on.…”
Section: Introductionmentioning
confidence: 99%
“…The measurements were made between 9:00 and 11:00 h. The following parameters were determined and calculated: the rate of net photosynthesis (PN) and transpiration (E), stomatal conductance (gs), and internal CO2 concentration (Ci). Apparent carboxylation efficiency (PN/Ci) was calculated according to Niu et al (2004), instantaneous (WUE, PN/E), and intrinsic water-use efficiencies (WUEi, PN/gs) according to Medrano et al (2015). The measurements included ten replicates per each treatment.…”
Section: Methodsmentioning
confidence: 99%